2015
DOI: 10.1002/mnfr.201400493
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonation of curcuminoids: Characterization and contribution of individual SULT enzymes

Abstract: This investigation contributed to elucidate the SULT-mediated metabolism and detoxication of curcuminoids at molecular levels and in different organs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Herein, genistein-7-glucoside has a higher affinity for β-glucosidase than quercetin-4′-glucoside thus the former shows a higher deglycosylation rate, whereas some other glycosides such as quercetin-3,4′-diglucoside, quercetin-3-glucoside, kaempferol-3-glucoside, quercetin-3-rhamnoglucoside, and naringenin-7-rhamnoglucoside prefer to remain unchanged (Day et al, 1998). This intracellular reaction is regarded as a vital way to expose hydroxyl group of xenobiotics for further conjugation Cheng et al (1999), Margaillan et al (2015), Wong et al (2009), Finel et al (2005), King et al (1999), Mostaghel et al (2016), King et al (2000), Teubner et al (2007), Cheng et al (1998), Cheng et al (1999), Barbier et al (2000), Knights et al (2013), Chimalakonda et al (2011), Riches et al (2009), Ghosh et al (2013), Sakamoto et al (2015), Lu et al (2015), Guidry et al (2017), Kurogi et al (2017),…”
Section: Phase II Metabolism In Enterocytesmentioning
confidence: 99%
“…Herein, genistein-7-glucoside has a higher affinity for β-glucosidase than quercetin-4′-glucoside thus the former shows a higher deglycosylation rate, whereas some other glycosides such as quercetin-3,4′-diglucoside, quercetin-3-glucoside, kaempferol-3-glucoside, quercetin-3-rhamnoglucoside, and naringenin-7-rhamnoglucoside prefer to remain unchanged (Day et al, 1998). This intracellular reaction is regarded as a vital way to expose hydroxyl group of xenobiotics for further conjugation Cheng et al (1999), Margaillan et al (2015), Wong et al (2009), Finel et al (2005), King et al (1999), Mostaghel et al (2016), King et al (2000), Teubner et al (2007), Cheng et al (1998), Cheng et al (1999), Barbier et al (2000), Knights et al (2013), Chimalakonda et al (2011), Riches et al (2009), Ghosh et al (2013), Sakamoto et al (2015), Lu et al (2015), Guidry et al (2017), Kurogi et al (2017),…”
Section: Phase II Metabolism In Enterocytesmentioning
confidence: 99%
“…Up to now, it is not known which of the SULT enzymes are responsible for the observed differences in curcumin sulfation between the two breast cancer lines. A very recent work showed that SULT1A3, SULT1C4, and SULT1E1 are the major isoforms catalyzing sulfation of curcumin; SULT1A1 and SULT2A1 demonstrated lower formation rates [23]. RT-PCR analysis in our lab revealed that only SUL-T1A1 mRNA levels were significantly higher in ZR-75-1 cells whereas SULT1A3 is equally expressed.…”
Section: Discussionmentioning
confidence: 56%
“…According to the reports, the enzyme that mediated drug sulfonation has a small binding pocket for binding flavonoids in a limited number of restrictive orientations; as a result, sulfonation only occurs at one hydroxyl position of flavonoids. [30,31] This strong regioselective sulfonation is different from UGT-mediated flavonoid glucuronidation. One UGT isoform (e.g.…”
Section: Discussionmentioning
confidence: 99%